The Role of the Tumor Microenvironment and Treatment Strategies in Colorectal Cancer - Chen, Yaping; Zheng, Xiao; Wu, Changping (Frontiers in Immunology, 2021)
Colorectal cancer (CRC) has the second highest mortality rate among all cancers worldwide. Surgery, chemotherapy, radiotherapy, molecular targeting and other treatment methods have significantly prolonged the survival of patients with CRC. Recently, the emergence of tumor immunotherapy represented by immune checkpoint inhibitors (ICIs) has brought new immunotherapy options for the treatment of advanced CRC. As the efficacy of ICIs is closely related to the tumor immune microenvironment (TME), it is necessary to clarify the relationship between the immune microenvironment of CRC and the efficacy of immunotherapy to ensure that the appropriate drugs are selected. We herein review the latest research progress in the immune microenvironment and strategies related to immunotherapy for CRC. We hope that this review helps in the selection of appropriate treatment strategies for CRC patients.